STATUS OF RECENT ENGLISHISMS IN THE LEXICAL FUND OF SECONDARY SCHOOL STUDENTS (Heritage, 2020)
Language change is an important characteristic of any language, and its manifestations are most obvious in the structure and content of the lexicon. One of the mechanisms which considerably change the outlook of a lexicon is the process of borrowing. The status of the English language nowadays, resulting from various historical circumstances, influences to a high degree many languages around the world, the Serbian language being no exception. The lexicon of the Serbian language has been changing not only as a result of various word formation processes, but also under the influence of the process of borrowing. Loanwords are being adopted and used in everyday oral and written communication, particularly by younger people, who are more open to accept changes. This paper investigates the status of some English loanwords among secondary school students, and how these words affect their lexicon. The aim of this research is to study which English loanwords have already been assimilated and perceived as words of domestic origin, and which words are still felt as foreign by the students. Through a set of tasks and questions, the students provided answers related to their own use of these words and how well they understand their original meaning. The analysis of the answers casts a deeper insight into the way loanwords are used in the target language the longer they stay therein.
Keywords: English loanwords, the Serbian language, assimilation, translation equivalent, semantic change, language contact.